Aspirations and investments in livestock: Evidence of aspiration failure in Kenya - Tabe-Ojong, Martin Paul Jr.; Heckelei, Thomas; Rasch, Sebastian (Wiley, 2023)
Aspirations influence future-oriented behavior and ensuing outcomes but they may also fail to do so when the aspired-to-status is far away from the current one. Theoretical predictions suggest an inverted U-shaped relationship between this aspiration gap and the effort to achieve what is aspired to. Aspirations that are ahead but not too far ahead of the current status serve as the best incentives for investments. We examine the income aspiration gap of smallholder households and relate it to livestock in a pastoral setting in Northern Kenya. Our focus on livestock is guided by the burgeoning recognition of livestock as an investment and saving conduit for many households in pastoral communities in developing nations. Employing different empirical strategies including parametric and semi-parametric techniques, we find livestock to be increasing with aspirations up to a threshold, from which it then declines to lead to an aspiration failure. Delving into livestock heterogeneity, we uncover evidence that cattle and poultry respond more to the aspiration gap than small ruminants such as sheep and goats. Different U-shaped tests confirm this relationship, bolstering the evidence of an aspiration failure. These findings are robust to the inclusion of relevant controls, truncations at zero, and different variable transformations. We also show that the findings are unlikely to be driven by unobserved heterogeneity. Additionally, we find that internal locus of control, that is the degree to which individuals believe they control outcomes in their lives is associated with livestock investments.